2012
DOI: 10.1155/2012/186353
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Phase Lag Index and Graph Analysis: Preliminary Investigation of Functional Connectivity during Resting State in Children

Abstract: Resting state functional connectivity of MEG data was studied in 29 children (9-10 years old). The weighted phase lag index (WPLI) was employed for estimating connectivity and compared to coherence. To further evaluate the network structure, a graph analysis based on WPLI was used to determine clustering coefficient (C) and betweenness centrality (BC) as local coefficients as well as the characteristic path length (L) as a parameter for global interconnectedness. The network's modular structure was also calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…S4(a), one-to-all connectivity). The results of EC resting-state functional connectivity were similar to those reported from a previous study (Ortiz et al, 2012). One-factor repeated-measures ANOVA (EC vs. EO vs. ITI) for the averaged WPLI value over Oz-to-all channel pairs revealed main effects of the baseline condition (F(2, 46) = 9.07, p b 0.001, η 2 = 0.28).…”
Section: Resting-state Eegsupporting
confidence: 87%
“…S4(a), one-to-all connectivity). The results of EC resting-state functional connectivity were similar to those reported from a previous study (Ortiz et al, 2012). One-factor repeated-measures ANOVA (EC vs. EO vs. ITI) for the averaged WPLI value over Oz-to-all channel pairs revealed main effects of the baseline condition (F(2, 46) = 9.07, p b 0.001, η 2 = 0.28).…”
Section: Resting-state Eegsupporting
confidence: 87%
“…It has been shown that wPLI outperforms PLI, coherence, and imaginary coherence in attenuating volume conduction using real local field potential data [Vinck et al 2011]. Moreover, wPLI has been demonstrated for measurement of inter-regional MEG synchrony in children [Dimitriadis et al 2013], including graph analysis of resting-state connectivity [Ortiz et al 2012].…”
Section: Estimating Functional Connectivity Using the Weighted Phasementioning
confidence: 99%
“…A variety of connectivity metrics have been developed to circumvent these problems. For example, the phase coherence (PC), the phase lag index (PLI), and imaginary coherence (icoh) of the MEG time courses have been used as connectivity measures (Hillebrand et al, 2012; Ortiz et al, 2012; Stam et al, 2009; Stam et al, 2007; Tewarie et al, 2013; Vinck et al, 2011). There have been several studies using these metrics to identify MEG source space networks.…”
Section: Introductionmentioning
confidence: 99%